Monitoring salt and sugar in food: an initiative to achieve reference values in Portugal - Dias, Maria da Graça (2019)
Objective: To contribute for drawing the baselines for the salt content of soups, breakfast cereals, bread and cheese, and the sugar content of yogurts and breakfast cereals in Portugal, in 2018. To gather evidence, for the Portuguese Governmental Authorities to support, validate and promote, near the industry, the necessary reductions to the values that are intended to be achieved in 2021.